PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL KOOPERATIF TIPE JIGSAW DI KELAS V SDN 20 PIAI KOTA PADANG - Asmaul Husnah Limbong; Mansurdin; Atri Waldi; Etri Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low learning outcomes in Pancasila Education at SDN 20 Piai Padang are caused by teacher-centered learning and a lack of student collaboration. This study aims to describe the improvement of student learning outcomes through the Jigsaw cooperative model. This Classroom Action Research (CAR) follows the Kemmis and McTaggart model, consisting of two cycles with four stages: planning, acting, observing, and reflecting. Data were collected through observation, tests, and non-tests. The results indicated that the quality of the teaching module increased from 83.3% (Cycle I) to 95.8% (Cycle II). Teacher activity improved from 81.2% to 87.5%, and student activity rose from 71.8% to 90.6%. The average student learning outcome significantly increased from 72.8 (Cycle I) to 88.5 (Cycle II). In conclusion, the Jigsaw model effectively enhances the quality of learning and students' academic achievement in elementary education.